Degradable colored PLA corn fiber

By combining polylactic acid slices and water-soluble polyester masterbatches with porous cuprous oxide nanoflower-ginkgo leaf extract composites, degradable colored PLA corn fibers with high repellency and continuous antibacterial effects were prepared, which solved the problem of existing corn fibers lacking antibacterial and anti-mosquito bites.

CN119777024APending Publication Date: 2025-04-08ZHEJIANG JINXIA NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510114402.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-01-15
Filing Date
2025-01-24
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing corn fiber products lack the antibacterial and anti-mosquito bites.

Method used

Degradable colored PLA corn fibers with high repellency and continuous antibacterial effects were prepared by combining with porous cuprous oxide nanoflower-ginkgo leaf extract composite materials using raw materials such as polylactic acid slices and water-soluble polyester masterbatches.

Benefits of technology

The high repellency rate and sustained durability of corn fiber have been achieved, and the antibacterial rate of Staphylococcus aureus, E. coli and Candida albicans has reached more than 90%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of textile production, and particularly relates to a degradable colored PLA corn fiber. Aiming at the problem that most of corn fibers in the prior art do not have the functions of resisting bacteria and preventing mosquito bites, the invention provides the degradable colored PLA corn fiber, the degradable colored PLA corn fiber comprises polylactic acid slices, and the repelling rate of the PLA corn fiber is greater than 85%; the test standard of the repelling rate is GB / T 24253-2009 evaluation of the anti-mite performance of the textile; after the PLA corn fiber is washed with water for 50 times, the bacteriostasis rate on staphylococcus aureus is greater than 90%, the bacteriostasis rate on escherichia coli is greater than 80%, and the bacteriostasis rate on candida albicans is greater than 70%; the test standard of the antibacterial rate is FZ / T 73023-2006, and the specific bacteria are as follows: the staphylococcus aureus is staphylococcus aureus ATCC6538, the escherichia coli is escherichia coli 8099, and the candida albicans is candida albicans ATCC10231. The corn fiber disclosed by the invention has a good repelling rate and a continuous and durable antibacterial effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textile production, and in particular relates to degradable colored PLA corn fiber. Background Art

[0002] Corn Fiber is a synthetic fiber made from corn, wheat and other starches, which is fermented into lactic acid, polymerized and spun. Corn fiber is made from lactic acid obtained from starch, and is a natural cycle-type, biodegradable fiber. This fiber does not use petroleum and other chemical raw materials at all. Its waste can be decomposed into carbon dioxide and water under the action of microorganisms in soil and seawater, and will not pollute the earth's environment. Since the initial raw material of this fiber is starch, its regeneration cycle is short, about one to two years, and the carbon dioxide produced can be reduced in the atmosphere by plant photosynthesis. Burning corn fiber almost does not produce nitric oxide, and its combustion heat is about one-third of polyethylene and polypropylene. Polylactic acid fiber is a lactic acid polymer synthesized from lactic acid contained in the human body, which is absolutely safe for the human body. According to tests, circular knitted fabrics made from corn fiber will not irritate the skin, are beneficial to human health, and have a sense of comfort.

[0003] Corn fiber has excellent performance, excellent drape, smoothness, moisture absorption and breathability, natural antibacterial and skin-safe weak acidity, good heat resistance and UV resistance, and rich gloss and elasticity. The drape, smoothness close to the skin, softness, hydrophilicity, and color gloss of corn fiber fabrics are well reflected, making corn fiber have significant development advantages in underwear, sportswear, etc. Corn fiber is blended with natural fibers such as cotton and wool to make new textile products. It has good shape retention, good gloss, silk-like excellent hand feel, good moisture absorption and quick drying effect, and has the effects of crispness, good elasticity, and beautiful gloss. In addition to being used as clothing, it can also be widely used in civil engineering, buildings, agriculture and forestry, aquaculture, papermaking, health care and household products, and biodegradable packaging materials.

[0004] With the increasing awareness of earth protection, energy depletion, safety and clothing hygiene, as well as the large-scale industrial production of corn particles or slices and the continuous expansion of corn fiber applications, many experts have recommended it as an environmental recycling material in the 21st century and an ecological fiber with great development potential. However, most of the corn fibers in the prior art do not have the functions of antibacterial and preventing mosquito bites.

[0005] For example, a Chinese invention patent application discloses a method for preparing corn fiber fabric [application number: 201510928476.6], which includes: 1) spinning corn fiber into corn fiber yarn; 2) spinning carbon fiber into carbon fiber yarn; 3) weaving the corn fiber yarn obtained in step (1) and the carbon fiber yarn obtained in step (2) into fabric on a loom in a manner of interweaving the warp yarn and the weft yarn into a three-up and three-down plain weave structure; 4) embossing the surface of the fabric obtained in step (3); 5) shaping and inspecting the fabric obtained in step (4).

[0006] The corn fiber fabric prepared in this invention application overcomes the characteristics of low strength and poor wear resistance by blending it with carbon fiber, but it still does not solve the above-mentioned problems. Summary of the invention

[0007] The purpose of the present invention is to provide a degradable colored PLA corn fiber in view of the above problems.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] A degradable colored PLA corn fiber, the raw material of which includes polylactic acid slices, and the repellency rate of the PLA corn fiber is greater than 85%;

[0010] The test standard for repellency rate is GB / T 24253-2009 Evaluation of anti-mite performance of textiles;

[0011] After being washed 50 times, the antibacterial rate of PLA corn fiber against Staphylococcus aureus was greater than 90%, the antibacterial rate of Escherichia coli was greater than 80%, and the antibacterial rate of Candida albicans was greater than 70%.

[0012] The test standard for the antibacterial rate is FZ / T 73023-2006 Antibacterial Knitwear, and the specific bacteria are: Staphylococcus aureus is Staphylococcus aureus ATCC6538, Escherichia coli is Escherichia coli 8099, and Candida albicans is Candida albicans ATCC10231.

[0013] In the above-mentioned degradable colored PLA corn fiber, the repellency rate of the PLA corn fiber is greater than 87%.

[0014] In the above-mentioned degradable colored PLA corn fiber, the repellency rate of the PLA corn fiber is greater than 89%.

[0015] In the above-mentioned degradable colored PLA corn fiber, the repellency rate of the PLA corn fiber is greater than 91%.

[0016] In the above-mentioned degradable colored PLA corn fiber, the repellency rate of the PLA corn fiber is greater than 93%.

[0017] In the above-mentioned degradable colored PLA corn fiber, the repellency rate of the PLA corn fiber is greater than 95%.

[0018] In the above-mentioned degradable colored PLA corn fiber, after being washed 50 times, the PLA corn fiber has an antibacterial rate of more than 92% against Staphylococcus aureus, more than 82% against Escherichia coli, and more than 72% against Candida albicans.

[0019] In the above-mentioned degradable colored PLA corn fiber, after being washed 50 times, the PLA corn fiber has an antibacterial rate of more than 95% against Staphylococcus aureus, more than 85% against Escherichia coli, and more than 75% against Candida albicans.

[0020] In the above-mentioned degradable colored PLA corn fiber, the raw materials of PLA corn fiber also include water-soluble polyester masterbatch, color masterbatch and compatibilizer; wherein the mass fraction of water-soluble polyester masterbatch in PLA corn fiber is 3-5%; the mass fraction of color masterbatch in PLA corn fiber is 0.5-1%, and the mass fraction of compatibilizer in PLA corn fiber is 0.25-0.5%. The color masterbatch can be color matched according to actual needs. The compatibilizer in the present invention is maleic anhydride grafted POE.

[0021] A processing method for degradable colored PLA corn fiber comprises the following technical steps: mixing various raw materials, melt-extruding the mixture, and then vacuum drying to obtain spinning masterbatch; and melt-spinning the spinning masterbatch to obtain PLA corn fiber.

[0022] The temperature of melt spinning is 215-265° C., the winding speed is 1400-1650 m / min, the drawing temperature is 65-80° C., and the drawing multiple is 2.5-3.0 times.

[0023] In the above-mentioned degradable colored PLA corn fiber, the preparation method of water-soluble polyester masterbatch comprises the following technical steps:

[0024] Step 1: Surface activation of porous cuprous oxide nanoflowers: disperse the porous cuprous oxide nanoflowers in anhydrous ethanol, and perform ultrasonic treatment for 1 to 2 hours to fully disperse them to obtain an activated porous cuprous oxide nanoflower dispersion; anhydrous ethanol is a good solvent that can effectively disperse the porous cuprous oxide nanoflowers and can be easily washed and removed in subsequent steps; the mass fraction of the porous cuprous oxide nanoflowers in anhydrous ethanol is 5 to 20%; the porous cuprous oxide nanoflowers in the present invention are prepared by the method described in the invention patent application with application number "201410746579.6".

[0025] Step 2: Silane coupling agent modification: Add silane coupling agent to the activated porous cuprous oxide nanoflower dispersion obtained in step 1 above. The silane coupling agent in the present invention uses 3-aminopropyltriethoxysilane, and continue stirring and reacting for 4 to 6 hours to obtain a modified porous cuprous oxide nanoflower dispersion; the mass ratio of the silane coupling agent to the porous cuprous oxide nanoflower in the activated porous cuprous oxide nanoflower dispersion is 1:30 to 1:40; this range provides enough silane coupling agent to achieve effective surface modification while avoiding waste and possible side effects caused by excessive use. The present invention allows the siloxane groups in the silane coupling agent to chemically react with the active sites on the surface of the porous cuprous oxide nanoflower to form a stable siloxane bond connection.

[0026] Step 3: Ginkgo leaf extract grafting: Add ginkgo leaf extract (CAS No.: 90045-36-6) to the modified porous cuprous oxide nanoflower dispersion prepared in step 2, keep the pH value at 5.0-7.0, stir and react for 12-48 hours at 22±1°C and in the dark; obtain the grafted porous cuprous oxide nanoflower dispersion; the mass ratio of the porous cuprous oxide nanoflower to the ginkgo leaf extract in the activated porous cuprous oxide nanoflower dispersion is 0.8:1-1:1; this ratio is mainly to consider that the porous cuprous oxide nanoflower has sufficient loading capacity, while avoiding excessive ginkgo leaf extract leading to decreased stability of the composite particles or waste of active ingredients. The active groups such as carboxyl and phenolic hydroxyl groups in the ginkgo leaf extract of the present invention undergo covalent bonding or ionic bonding, ensuring that the amino groups on the silane coupling agent are successfully connected to the effective ingredients of the ginkgo leaf extract to form a stable chemical bond.

[0027] Step 4: product separation and washing: the grafted porous cuprous oxide nanoflower dispersion obtained in step 3 is centrifuged to obtain a precipitate, which is washed alternately with anhydrous ethanol and deionized water for 6 to 10 times, and then dried in a vacuum drying oven to obtain a porous cuprous oxide nanoflower-ginkgo leaf extract composite material;

[0028] Step 5: Preparation of water-soluble polyester masterbatch: The porous cuprous oxide nanoflower-ginkgo leaf extract composite material and water-soluble polyester chips prepared in step 4 are melt-extruded and granulated to obtain water-soluble polyester masterbatch. The mass fraction of the porous cuprous oxide nanoflower-ginkgo leaf extract composite material in the water-soluble polyester masterbatch is 15% to 25%. The water-soluble polyester chips in the present invention are PVA slurry water-soluble polyester chips produced by Jinan Tangcai Chemical Products Co., Ltd.

[0029] The flavonoids and phenolic acid compounds in Ginkgo biloba extract are lipophilic and can bind tightly to the lipid molecules on the bacterial and mite cell membranes, resulting in decreased stability of the membrane structure and increased permeability. This effect may lead to leakage of cell contents and electrolyte imbalance, ultimately affecting the normal metabolism and proliferation of cells, and even causing cell rupture and death. Ginkgo biloba extract has a strong antioxidant capacity, can scavenge free radicals, and inhibit lipid peroxidation. For mites, the antioxidant effect may interfere with their oxidative stress response in the body, affecting their energy metabolism and survival. In addition, antioxidant activity may also indirectly inhibit bacterial growth, because many bacteria rely on redox reactions for energy metabolism.

[0030] The physical adsorption effect of porous cuprous oxide nanoflowers is combined with the biologically active components of ginkgo leaf extract to enhance the adsorption capacity for bacteria and mites and improve the antibacterial and mite removal efficiency.

[0031] The oxidative damage effect of porous cuprous oxide nanoflowers and the multiple bioactive components of ginkgo leaf extract complement each other and can produce a broader inhibitory effect on different types of microorganisms or mites.

[0032] Compared with the prior art, the advantages of the present invention are:

[0033] 1. The corn fiber of the present invention has a good repellency rate and a sustained and durable antibacterial effect.

[0034] 2. The present invention uses porous cuprous oxide nanoflowers as carriers to slowly release the active ingredients in the ginkgo leaf extract, prolong its effective action time in the application environment, and improve the durability of antibacterial and mite removal. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with specific implementation methods.

[0036] Example 1

[0037] This embodiment provides a degradable colored PLA corn fiber, the raw materials of which include water-soluble polyester masterbatch, maleic anhydride grafted POE, color masterbatch and polylactic acid chips, wherein the mass fraction of the water-soluble polyester masterbatch in the PLA corn fiber is 3%; the mass fraction of the color masterbatch in the PLA corn fiber is 0.5%, the mass fraction of the maleic anhydride grafted POE in the PLA corn fiber is 0.25%, and the remaining component is polylactic acid chips. The color masterbatch can be color matched according to actual needs.

[0038] A method for processing degradable colored PLA corn fiber comprises the following technical steps: mixing various raw materials, melt-extruding the mixture, and then vacuum drying to obtain spinning masterbatch; and melt-spinning the spinning masterbatch to obtain corn fiber.

[0039] The melt spinning temperature was 215°C, the winding speed was 1400 m / min, the drawing temperature was 65°C, and the drawing multiple was 2.5 times.

[0040] A method for preparing a water-soluble polyester masterbatch, comprising the following technical steps:

[0041] 1. Surface activation of porous cuprous oxide nanoflowers: The porous cuprous oxide nanoflowers were dispersed in anhydrous ethanol and subjected to ultrasonic treatment for 1 hour to fully disperse them, thereby obtaining an activated porous cuprous oxide nanoflower dispersion. Anhydrous ethanol, as a good solvent, can effectively disperse the porous cuprous oxide nanoflowers and can be easily washed and removed in subsequent steps. The mass fraction of the porous cuprous oxide nanoflowers in anhydrous ethanol is 5%.

[0042] 2. Silane coupling agent modification: Add 3-aminopropyltriethoxysilane to the porous cuprous oxide nanoflower dispersion activated in step 1 above, and continue stirring and reacting for 4 hours to obtain a modified porous cuprous oxide nanoflower dispersion;

[0043] The mass ratio of the silane coupling agent to the porous cuprous oxide nanoflowers in the activated porous cuprous oxide nanoflower dispersion is 1:30; this range provides sufficient silane coupling agent to achieve effective surface modification while avoiding waste and possible side effects caused by excess.

[0044] 3. Ginkgo leaf extract grafting: Add ginkgo leaf extract to the modified porous cuprous oxide nanoflower dispersion obtained in step 2, keep the pH value at 5.0, stir and react for 12 hours at 21°C and in the dark, and obtain a grafted porous cuprous oxide nanoflower dispersion;

[0045] The mass ratio of porous cuprous oxide nanoflowers to ginkgo leaf extract in the activated porous cuprous oxide nanoflower dispersion is 0.8:1; this ratio is mainly to ensure that the porous cuprous oxide nanoflowers have sufficient loading capacity while avoiding excessive ginkgo leaf extract that leads to decreased stability of the composite particles or waste of active ingredients.

[0046] The active groups such as carboxyl and phenolic hydroxyl groups in the ginkgo leaf extract of the present application are covalently bonded or ionically bonded to ensure that the amino groups on the silane coupling agent are successfully connected to the effective ingredients of the ginkgo leaf extract to form a stable chemical bond.

[0047] 4. Product separation and washing: The porous cuprous oxide nanoflower dispersion after grafting in step 3 is centrifuged to obtain a precipitate, and then washed with anhydrous ethanol and deionized water alternately for 6 times to remove unreacted silane coupling agent and impurities; and then dried in a vacuum drying oven to obtain a porous cuprous oxide nanoflower-ginkgo leaf extract composite material;

[0048] 5. Preparation of water-soluble polyester masterbatch: The porous cuprous oxide nanoflower-ginkgo leaf extract composite material prepared in step 4 and the water-soluble polyester chips (PVA slurry water-soluble polyester chips produced by Jinan Tangcai Chemical Products Co., Ltd.) are melt-extruded and granulated to obtain a water-soluble polyester masterbatch; wherein the mass fraction of the porous cuprous oxide nanoflower-ginkgo leaf extract composite material in the water-soluble polyester masterbatch is 15%.

[0049] The test results of Example 1 are as follows: the repellency rate of PLA corn fiber is 86%;

[0050] For the test standard of repellency rate, please refer to GB / T 24253-2009 Evaluation of anti-mite performance of textiles;

[0051] After being washed 50 times, the antibacterial rates of corn fiber against Staphylococcus aureus were 91%, Escherichia coli were 81%, and Candida albicans were 76%.

[0052] The test of the antibacterial rate refers to the standard FZ / T 73023-2006 Antibacterial knitwear, and the specific bacteria are: Staphylococcus aureus is Staphylococcus aureus ATCC6538, Escherichia coli is Escherichia coli 8099, and Candida albicans is Candida albicans ATCC10231.

[0053] Example 2

[0054] This embodiment provides a degradable colored PLA corn fiber, the raw materials of which include water-soluble polyester masterbatch, maleic anhydride grafted POE, color masterbatch and polylactic acid slices, wherein the mass fraction of the water-soluble polyester masterbatch in the PLA corn fiber is 4%; the mass fraction of the color masterbatch in the PLA corn fiber is 0.75%, and the mass fraction of the maleic anhydride grafted POE in the PLA corn fiber is 0.35%. The color masterbatch can be color matched according to actual needs.

[0055] A method for processing degradable colored PLA corn fiber comprises the following technical steps: mixing various raw materials, melt-extruding the mixture, and then vacuum drying to obtain spinning masterbatch; and melt-spinning the spinning masterbatch to obtain corn fiber.

[0056] The melt spinning temperature was 240°C, the winding speed was 1500 m / min, the drawing temperature was 75°C, and the drawing multiple was 2.8 times.

[0057] A method for preparing a water-soluble polyester masterbatch, comprising the following technical steps:

[0058] 1. Surface activation of porous cuprous oxide nanoflowers: The porous cuprous oxide nanoflowers were dispersed in anhydrous ethanol and subjected to ultrasonic treatment for 1.5 hours to fully disperse them, thereby obtaining an activated porous cuprous oxide nanoflower dispersion. Anhydrous ethanol, as a good solvent, can effectively disperse the porous cuprous oxide nanoflowers and can be easily washed and removed in subsequent steps. The mass fraction of the porous cuprous oxide nanoflowers in anhydrous ethanol is 10%.

[0059] 2. Silane coupling agent modification: Add 3-aminopropyltriethoxysilane to the porous cuprous oxide nanoflower dispersion activated in step 1 above, and continue stirring and reacting for 5 hours to obtain a modified porous cuprous oxide nanoflower dispersion;

[0060] The mass ratio of 3-aminopropyltriethoxysilane to the porous cuprous oxide nanoflowers in the activated porous cuprous oxide nanoflower dispersion is 1:35; this range provides sufficient silane coupling agent to achieve effective surface modification while avoiding waste and possible side effects caused by excess.

[0061] 3. Ginkgo leaf extract grafting: Add ginkgo leaf extract to the modified porous cuprous oxide nanoflower dispersion obtained in step 2, keep the pH value at 6.0, stir and react for 30 hours at 22°C and in the dark, and obtain a grafted porous cuprous oxide nanoflower dispersion;

[0062] The mass ratio of porous cuprous oxide nanoflowers to ginkgo leaf extract in the activated porous cuprous oxide nanoflower dispersion is 0.8:0.9; this ratio is mainly to ensure that the porous cuprous oxide nanoflowers have sufficient loading capacity while avoiding excessive ginkgo leaf extract that leads to decreased stability of the composite particles or waste of active ingredients.

[0063] The active groups such as carboxyl and phenolic hydroxyl groups in the ginkgo leaf extract of the present application are covalently bonded or ionically bonded to ensure that the amino groups on the silane coupling agent are successfully connected to the effective ingredients of the ginkgo leaf extract to form a stable chemical bond.

[0064] 4. Product separation and washing: The porous cuprous oxide nanoflower dispersion after grafting in step 3 is centrifuged to obtain a precipitate, and then washed 8 times with anhydrous ethanol and deionized water alternately to remove unreacted silane coupling agent and impurities; then dried in a vacuum drying oven to obtain a porous cuprous oxide nanoflower-ginkgo leaf extract composite material;

[0065] 5. Preparation of water-soluble polyester masterbatch: The porous cuprous oxide nanoflower-ginkgo leaf extract composite material prepared in step 4 and the water-soluble polyester chips are melt-extruded and granulated to obtain a water-soluble polyester masterbatch; wherein the mass fraction of the porous cuprous oxide nanoflower-ginkgo leaf extract composite material in the water-soluble polyester masterbatch is 20%.

[0066] The test results of Example 2 are as follows: the repellency rate of PLA corn fiber is 88%;

[0067] For the test standard of repellency rate, please refer to GB / T 24253-2009 Evaluation of anti-mite performance of textiles;

[0068] After being washed 50 times, the antibacterial rate of corn fiber against Staphylococcus aureus was 95%, the antibacterial rate against Escherichia coli was 86%, and the antibacterial rate against Candida albicans was 82%.

[0069] The test of the antibacterial rate refers to the standard FZ / T 73023-2006 Antibacterial knitwear, and the specific bacteria are: Staphylococcus aureus is Staphylococcus aureus ATCC6538, Escherichia coli is Escherichia coli 8099, and Candida albicans is Candida albicans ATCC10231.

[0070] Example 3

[0071] This embodiment provides a degradable colored PLA corn fiber, the raw materials of which include water-soluble polyester masterbatch, maleic anhydride grafted POE, color masterbatch and polylactic acid slices, wherein the mass fraction of the water-soluble polyester masterbatch in the PLA corn fiber is 5%, the mass fraction of the color masterbatch in the PLA corn fiber is 1%, and the mass fraction of the maleic anhydride grafted POE in the PLA corn fiber is 0.5%. The color masterbatch can be color matched according to actual needs.

[0072] A method for processing degradable colored PLA corn fiber comprises the following technical steps: mixing various raw materials, melt-extruding the mixture, and then vacuum drying to obtain spinning masterbatch; and melt-spinning the spinning masterbatch to obtain corn fiber.

[0073] The melt spinning temperature was 265°C, the winding speed was 1650 m / min, the drawing temperature was 80°C, and the drawing multiple was 3.0 times.

[0074] A method for preparing a water-soluble polyester masterbatch, comprising the following technical steps:

[0075] 1. Surface activation of porous cuprous oxide nanoflowers: The porous cuprous oxide nanoflowers were dispersed in anhydrous ethanol and subjected to ultrasonic treatment for 2 hours to fully disperse them, thereby obtaining an activated porous cuprous oxide nanoflower dispersion. Anhydrous ethanol, as a good solvent, can effectively disperse the porous cuprous oxide nanoflowers and can be easily washed and removed in subsequent steps. The mass fraction of the porous cuprous oxide nanoflowers in anhydrous ethanol is 20%.

[0076] 2. Silane coupling agent modification: Add 3-aminopropyltriethoxysilane to the porous cuprous oxide nanoflower dispersion activated in step 1 above, and continue stirring and reacting for 6 hours to obtain a modified porous cuprous oxide nanoflower dispersion;

[0077] The mass ratio of 3-aminopropyltriethoxysilane to the porous cuprous oxide nanoflowers in the activated porous cuprous oxide nanoflower dispersion is 1:40; this range provides sufficient silane coupling agent to achieve effective surface modification while avoiding waste and possible side effects caused by excess.

[0078] 3. Ginkgo leaf extract grafting: add ginkgo leaf extract to the modified porous cuprous oxide nanoflower dispersion obtained in step 2, keep the pH value at 7.0, stir and react for 48 hours at 23°C and in the dark, and obtain a grafted porous cuprous oxide nanoflower dispersion;

[0079] The mass ratio of porous cuprous oxide nanoflowers to ginkgo leaf extract in the activated porous cuprous oxide nanoflower dispersion is 1:1; this ratio is mainly to ensure that the porous cuprous oxide nanoflowers have sufficient loading capacity while avoiding excessive ginkgo leaf extract that leads to decreased stability of the composite particles or waste of active ingredients.

[0080] The active groups such as carboxyl and phenolic hydroxyl groups in the ginkgo leaf extract of the present application are covalently bonded or ionically bonded to ensure that the amino groups on the silane coupling agent are successfully connected to the effective ingredients of the ginkgo leaf extract to form a stable chemical bond.

[0081] 4. Product separation and washing: The porous cuprous oxide nanoflower dispersion after grafting in step 3 is centrifuged to obtain a precipitate, and then washed 10 times alternately with anhydrous ethanol and deionized water to remove unreacted silane coupling agent and impurities; and then dried in a vacuum drying oven to obtain a porous cuprous oxide nanoflower-ginkgo leaf extract composite material;

[0082] 5. Preparation of water-soluble polyester masterbatch: The porous cuprous oxide nanoflower-ginkgo leaf extract composite material prepared in step 4 and the water-soluble polyester chips are melt-extruded and granulated to obtain a water-soluble polyester masterbatch; wherein the mass fraction of the porous cuprous oxide nanoflower-ginkgo leaf extract composite material in the water-soluble polyester masterbatch is 25%.

[0083] The test results of Example 3 are as follows: the repellency rate of corn fiber is 92%;

[0084] For the test standard of repellency rate, please refer to GB / T 24253-2009 Evaluation of anti-mite performance of textiles;

[0085] After being washed 50 times, the antibacterial rate of corn fiber against Staphylococcus aureus was 96%, the antibacterial rate against Escherichia coli was 89%, and the antibacterial rate against Candida albicans was 87%.

[0086] The test of the antibacterial rate refers to the standard FZ / T 73023-2006 Antibacterial knitwear, and the specific bacteria are: Staphylococcus aureus is Staphylococcus aureus ATCC6538, Escherichia coli is Escherichia coli 8099, and Candida albicans is Candida albicans ATCC10231.

[0087] Comparative Example 1

[0088] This comparative example provides a degradable colored PLA corn fiber, the raw materials of which include water-soluble polyester masterbatch, maleic anhydride grafted POE, color masterbatch and polylactic acid slices, wherein the mass fraction of the water-soluble polyester masterbatch in the PLA corn fiber is 4%; the mass fraction of the color masterbatch in the PLA corn fiber is 0.75%, and the mass fraction of the maleic anhydride grafted POE in the PLA corn fiber is 0.35%. The color masterbatch can be color matched according to actual needs.

[0089] A method for processing degradable colored PLA corn fiber comprises the following technical steps: mixing various raw materials, melt-extruding the mixture, and then vacuum drying to obtain spinning masterbatch; and melt-spinning the spinning masterbatch to obtain corn fiber.

[0090] The melt spinning temperature was 240°C, the winding speed was 1500 m / min, the drawing temperature was 75°C, and the drawing multiple was 2.8 times.

[0091] A method for preparing a water-soluble polyester masterbatch, comprising the following technical steps:

[0092] 1. Mixing: The porous cuprous oxide nanoflowers and the ginkgo leaf extract are mixed to obtain a porous cuprous oxide nanoflower-ginkgo leaf extract composite material;

[0093] The mass ratio of porous cuprous oxide nanoflowers to ginkgo biloba extract is 0.8:0.9;

[0094] 2. Preparation of water-soluble polyester masterbatch: The porous cuprous oxide nanoflower-ginkgo leaf extract composite material prepared in step 2 and the water-soluble polyester chips are melt-extruded and granulated to obtain a water-soluble polyester masterbatch; wherein the mass fraction of the porous cuprous oxide nanoflower-ginkgo leaf extract composite material in the water-soluble polyester masterbatch is 20%.

[0095] The test results of Comparative Example 1 are as follows: the repellency rate of PLA corn fiber is 62%;

[0096] For the test standard of repellency rate, please refer to GB / T 24253-2009 Evaluation of anti-mite performance of textiles;

[0097] After being washed 50 times, the antibacterial rate of corn fiber against Staphylococcus aureus was 65%, the antibacterial rate against Escherichia coli was 58%, and the antibacterial rate against Candida albicans was 53%.

[0098] The test of the antibacterial rate refers to the standard FZ / T 73023-2006 Antibacterial knitwear, and the specific bacteria are: Staphylococcus aureus is Staphylococcus aureus ATCC6538, Escherichia coli is Escherichia coli 8099, and Candida albicans is Candida albicans ATCC10231.

[0099] Comparative Example 2

[0100] This comparative example provides a degradable colored PLA corn fiber, the raw materials of which include water-soluble polyester masterbatch, maleic anhydride grafted POE, color masterbatch and polylactic acid slices, wherein the mass fraction of the water-soluble polyester masterbatch in the PLA corn fiber is 1%; the mass fraction of the color masterbatch in the PLA corn fiber is 0.75%, and the mass fraction of the maleic anhydride grafted POE in the PLA corn fiber is 0.35%. The color masterbatch can be color matched according to actual needs.

[0101] A method for processing degradable colored PLA corn fiber, same as Example 2.

[0102] The test results of Comparative Example 2 are as follows: the repellency rate of PLA corn fiber is 79%;

[0103] For the test standard of repellency rate, please refer to GB / T 24253-2009 Evaluation of anti-mite performance of textiles;

[0104] After being washed 50 times, the antibacterial rates of corn fiber against Staphylococcus aureus were 82%, Escherichia coli were 73%, and Candida albicans were 68%.

[0105] The test of the antibacterial rate refers to the standard FZ / T 73023-2006 Antibacterial knitwear, and the specific bacteria are: Staphylococcus aureus is Staphylococcus aureus ATCC6538, Escherichia coli is Escherichia coli 8099, and Candida albicans is Candida albicans ATCC10231.

[0106] Comparative Example 3

[0107] This comparative example provides a degradable colored PLA corn fiber, the raw materials of which include water-soluble polyester masterbatch, maleic anhydride grafted POE, color masterbatch and polylactic acid slices, wherein the mass fraction of the water-soluble polyester masterbatch in the PLA corn fiber is 2%; the mass fraction of the color masterbatch in the PLA corn fiber is 0.75%, and the mass fraction of the maleic anhydride grafted POE in the PLA corn fiber is 0.35%. The color masterbatch can be color matched according to actual needs.

[0108] A method for processing degradable colored PLA corn fiber, same as Example 2.

[0109] The test results of Comparative Example 2 are as follows: the repellency rate of PLA corn fiber is 83%;

[0110] For the test standard of repellency rate, please refer to GB / T 24253-2009 Evaluation of anti-mite performance of textiles;

[0111] After being washed 50 times, the corn fiber had an antibacterial rate of 85% against Staphylococcus aureus, 76% against Escherichia coli, and 72% against Candida albicans.

[0112] The test of the antibacterial rate refers to the standard FZ / T 73023-2006 Antibacterial knitwear, and the specific bacteria are: Staphylococcus aureus is Staphylococcus aureus ATCC6538, Escherichia coli is Escherichia coli 8099, and Candida albicans is Candida albicans ATCC10231.

[0113] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A degradable colored PLA corn fiber, characterized in that: Its raw materials include polylactic acid chips, and the repellency rate of PLA corn fiber is greater than 85%; The test standard for repellency rate is GB / T 24253-2009 Evaluation of anti-mite performance of textiles; After being washed 50 times, the antibacterial rate of PLA corn fiber against Staphylococcus aureus was greater than 90%, the antibacterial rate of Escherichia coli was greater than 80%, and the antibacterial rate of Candida albicans was greater than 70%. The test standard for the antibacterial rate is FZ / T 73023-2006 Antibacterial Knitwear, and the specific bacteria are: Staphylococcus aureus is Staphylococcus aureus ATCC6538, Escherichia coli is Escherichia coli 8099, and Candida albicans is Candida albicans ATCC10231.

2. The degradable colored PLA corn fiber according to claim 1, characterized in that: The repellency of PLA corn fiber is greater than 87%.

3. The degradable colored PLA corn fiber according to claim 1, characterized in that: The repellency of PLA corn fiber is greater than 89%.

4. The degradable colored PLA corn fiber according to claim 1, characterized in that: The repellency of PLA corn fiber is greater than 91%.

5. The degradable colored PLA corn fiber according to claim 1, characterized in that: The repellency of PLA corn fiber is greater than 93%.

6. The degradable colored PLA corn fiber according to claim 1, characterized in that: The repellency of PLA corn fiber is greater than 95%.

7. The degradable colored PLA corn fiber according to claim 1, characterized in that: After being washed 50 times, the PLA corn fiber has an antibacterial rate of more than 92% against Staphylococcus aureus, more than 82% against Escherichia coli, and more than 72% against Candida albicans.

8. The degradable colored PLA corn fiber according to claim 1, characterized in that: After being washed 50 times, the PLA corn fiber has an antibacterial rate of more than 95% against Staphylococcus aureus, more than 85% against Escherichia coli, and more than 75% against Candida albicans.

9. The degradable colored PLA corn fiber according to claim 1, characterized in that: The raw materials of PLA corn fiber also include water-soluble polyester masterbatch, color masterbatch and compatibilizer; wherein the mass fraction of the water-soluble polyester masterbatch in the PLA corn fiber is 3-5%; the mass fraction of the color masterbatch in the PLA corn fiber is 0.5-1%; and the mass fraction of the compatibilizer in the PLA corn fiber is 0.25-0.5%.

10. The degradable colored PLA corn fiber according to claim 9, characterized in that: The preparation method of water-soluble polyester masterbatch comprises the following technical steps: Step 1: Surface activation of porous cuprous oxide nanoflowers: disperse the porous cuprous oxide nanoflowers in anhydrous ethanol and perform ultrasonic treatment for 1 to 2 hours to fully disperse the porous cuprous oxide nanoflowers to obtain an activated porous cuprous oxide nanoflower dispersion; Step 2: Silane coupling agent modification: Add silane coupling agent to the activated porous cuprous oxide nanoflower dispersion prepared in step 1 above, and continue stirring and reacting for 4 to 6 hours to obtain a modified porous cuprous oxide nanoflower dispersion; Step 3: Ginkgo leaf extract grafting: Add ginkgo leaf extract to the modified porous cuprous oxide nanoflower dispersion prepared in step 2, keep the pH value at 5.0-7.0, stir and react for 12-48 hours at 22±1°C and in the dark, and obtain a grafted porous cuprous oxide nanoflower dispersion; Step 4: product separation and washing: the grafted porous cuprous oxide nanoflower dispersion obtained in step 3 is centrifuged to obtain a precipitate, which is washed alternately with anhydrous ethanol and deionized water for 6 to 10 times, and then dried in a vacuum drying oven to obtain a porous cuprous oxide nanoflower-ginkgo leaf extract composite material; Step 5: Preparation of water-soluble polyester masterbatch: The porous cuprous oxide nanoflower-ginkgo leaf extract composite material and water-soluble polyester chips prepared in step 4 are melt-extruded and granulated to obtain water-soluble polyester masterbatch.

Citation Information

Patent Citations

  • Corn fiber fabric preparing method

    CN105332140A

  • Preparation method of layered flower-like cuprous oxide nanomaterial

    CN105883893A